Layer- and column-specific knockout of NMDA receptors in pyramidal neurons of the mouse barrel cortex. - Aronoff, Rachel; Petersen, Carl (Frontiers in Integrative Neuroscience, 2007)
Viral vectors injected into the mouse brain offer the possibility for localized genetic modifications in a highly controlled manner. Lentivector injection into mouse neocortex transduces cells within a diameter of approximately 200µm, which closely matches the lateral scale of a column in barrel cortex. The depth and volume of the injection determines which cortical layer is transduced. Furthermore, transduced gene expression from the lentivector can be limited to predominantly pyramidal neurons by using a 1.3kb fragment of the αCaMKII promoter. This technique therefore allows genetic manipulation of a specific cell type in defined columns and layers of the neocortex. By expressing Cre recombinase from such a lentivector in gene-targeted mice carrying a floxed gene, highly specific genetic lesions can be induced. Here, we demonstrate the utility of this approach by specifically knocking out NMDA receptors (NMDARs) in pyramidal neurons in the somatosensory barrel cortex of gene-targeted mice carrying floxed NMDAR 1 genes. Neurons transduced with lentivector encoding GFP and Cre recombinase exhibit not only reductions in NMDAR 1 mRNA levels, but reduced NMDAR-dependent currents and pairing-induced synaptic potentiation. This technique for knockout of NMDARs in a cell type, column- and layer-specific manner in the mouse somatosensory cortex may help further our understanding of the functional roles of NMDARs in vivo during sensory perception and learning.